Sedimentological analysis of the Ordovician and Devonian basins in southern Peru and northern Bolivia - Reimann Zumsprekel, Cornelia R. (2006)
We present data from a study of the evolution of the Early Paleozoic Peru-Bolivia Trough, its facies development and the provenance of sediments deposited during Ordovician and Devonian time. We measured and sampled sections in the Ordovician successions in the Cordillera Oriental of southern Peru (Ollantaytambo, Verónica, San José, Sandia and Calapuja Formations) and northern Bolivia (Coroico, Amutara and Cancañiri Formations), and in the Upper Silurian to Devonian Lampa Formation on the Altiplano, and the Devonian Cabanillas Group on the Altiplano and the Peruvian Coastal Cordillera (Arequipa Massif). Our data contribute to a better understanding of the plate tectonic evolution of the Western Gondwana margin during early Paleozoic times.